2017
DOI: 10.3389/fpls.2016.02018
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel SSR Markers for Flax (Linum usitatissimum L.) Using Reduced-Representation Genome Sequencing

Abstract: Flax (Linum usitatissimum L.) is a major fiber and oil yielding crop grown in northeastern China. Identification of flax molecular markers is a key step toward improving flax yield and quality via marker-assisted breeding. Simple sequence repeat (SSR) markers, which are based on genomic structural variation, are considered the most valuable type of genetic marker for this purpose. In this study, we screened 1574 microsatellites from Linum usitatissimum L. obtained using reduced representation genome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
6
18
0
2
Order By: Relevance
“…RNA-Seq data demonstrated that three genes were enriched after ABA treatment and seven after the application of diniconazole. Similar results have been previously observed in Dendrobium officinale 52 and Poa pratensis 53 exposed to abiotic stress conditions. These results indicate that WR04-6 can respond to ABA by actively regulating glycolysis and TCA cycle pathway-related genes and enzyme activities.…”
Section: Discussionsupporting
confidence: 91%
“…RNA-Seq data demonstrated that three genes were enriched after ABA treatment and seven after the application of diniconazole. Similar results have been previously observed in Dendrobium officinale 52 and Poa pratensis 53 exposed to abiotic stress conditions. These results indicate that WR04-6 can respond to ABA by actively regulating glycolysis and TCA cycle pathway-related genes and enzyme activities.…”
Section: Discussionsupporting
confidence: 91%
“…The polymorphism rate was 40.70%, which was lower than that of pepper (67.4%) [28], cucumber (54.81%) [34], and Brassica rapa (77%) [26]. Additionally, the PIC obtained was low (0.3097), which was consistent with the results reported by previous studies [10,13,14]. This indicated that InDel was more suitable for the identi cation of ax germplasm resources, since the degree of variation of ax genes was not substantial and the genetic background was narrow.…”
Section: Discussionsupporting
confidence: 89%
“…(1,651,856) [28], the number of InDels detected in this study was low but was higher than that of cucumber (Cucumis sativus) (10,470) [34] and sesame (Sesamum indicum L.) (7,477) [37]. Compared with other markers in ax, the number of InDels was less than that of SNPs [16,19] and more than most SSR markers [8,10,13,43]. The main reason for obtaining such results may be attributed to the fact that compared with the complicated operations of RAPD, AFLP, and SSR, the use of a re-sequencing technology can aid an easy detection and obtainment of a larger number and higher quality of SNPs and InDels in the whole genome.…”
Section: Discussionmentioning
confidence: 86%
“…Due to its relatively higher density, excellent consistency, effectiveness, and lower cost when compared with traditional methods, this method has become a popular genotyping method. Indeed, in our previous study SLAF-seq technology was used to develop numerous novel SSRs in flax (Wu et al, 2017 ). Subsequently, in this work sequencing results provided a large quantity of SLAF markers to further drive flax genomic research.…”
Section: Discussionmentioning
confidence: 99%